Public private partnership (PPP) in infrastructure provision - BERKOH, Alfred Nuako Kwame (KDI School, 2017)
The overall significance of infrastructure to sustainable development cannot be overemphasized and thus continues to remain a critical component for development. While the issues of globalization and urbanization continue to emphasize the need to expand existing infrastructure, budgetary constraints amongst other factors have also increased the need for alternative source of funding to meet the infrastructure gap. Particularly for the Sub-Saharan Africa (SSA), the infrastructure gap continues to remain a significant restraint to its development. Consequently, Public Private Partnership (PPP) has evolved as an alternative financing tool and a growing trend for infrastructure financing yet remains an underdeveloped paradigm in the SSA region. This report thus analyses the key determinants for private sector engagement in PPP in Sub-Saharan Africa with critical emphasis on the macroeconomic situation, favorable market conditions, governance and political climate as well as the regulatory and institutional environment as key determinants. This study uses a cross-country panel data using random effects regression with the outcome variable being the total amount of investment on private participation for infrastructure (logged) from 2005 to 2014. As expected, the study revealed that the favorable market conditions, using population size and the GDP per capita as proxies, as well as the quality institutions for effective and efficient service delivery are the most significant determinant of PPP investments for the SSA region. However, in contrast to the assumption of the study, aid and higher regulatory burden those were not anticipated to positively impact PPP investments rather significantly influenced PPP investments in the region. In line with these findings, it is recommended that policies that significantly improve the market conditions should be designed and formulated while building on institutional capacity and experience to implement PPP related policies and programs. Also, policy makers as well as international and regional agencies should design policies that will seek to advance long term PPP investments in an adequately regulated business environment as well as provide guarantees and other risk management mechanism to foster private sector investments amidst the weak regulatory environment that may exist. Although the model specifications is preliminary, we believe the findings and discussions herewith significantly contribute to existing literature particularly considering the fact that very limited studies have been conducted on the SSA region on the subject matter.
Thesis(Master) --KDI School:Master of Development Policy,2017